Pemikiran Baru Pandangan Teologi: Substantif, Relasional, dan Fungsional Tentang Gambar Rupa Allah - Dewi, Ester Yunita; Baskoro, Paulus Kunto (Sekolah Tinggi Teologi Berita Hidup, 2025)
Theological study of the image of God helps to understand the two words, words that are not different in meaning, but reinforce each other. The topic of the image and likeness of God has produced three popular views, namely the substantial, relational and functional views. Each of these three views has advantages and disadvantages. The aim of the research is to present a third view in a balanced way and to develop new thinking apart from conducting comparative and evaluation studies. Methode search as methode kualitatif deskritif. The findings of this study indicate that: First, the image of God is a fully Man. The results of the research on the word image and likeness in Genesis 1:26-31, 5:1-3 and 9:6 prove that the use of the words